2017
DOI: 10.2355/isijinternational.isijint-2017-377
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Swirling Flow Producer in a Conventional Tundish during Continuous Casting of Steel

Abstract: A swirling flow producer was designed for a conventional tundish in order to produce a swirling flow in the SEN driven by the steel flow potential. CFD simulations were carried out to investigate the flow phenomena in the new tundish system. The results show that a swirling flow in the tundish SEN was successfully obtained. The swirl number of the obtained steel flow inside the SEN can reach a value of 1.34, with a tangential velocity of around 2.8 m/s. The possibility of slag entrainment at the top of the tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…This is due to that the swirling flow in the SEN is not completely axisymmetric, as shown in Figure 1. However, the flow symmetry can be further improved by the cylindrical tundish design, such as using two tangential inlets in the cylindrical tundish in Figure 1a, which was investigated in a previous study [67]. For the study on M-EMS application, it was also found that the distribution of the electromagnetic force is not uniform in space [33].…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to that the swirling flow in the SEN is not completely axisymmetric, as shown in Figure 1. However, the flow symmetry can be further improved by the cylindrical tundish design, such as using two tangential inlets in the cylindrical tundish in Figure 1a, which was investigated in a previous study [67]. For the study on M-EMS application, it was also found that the distribution of the electromagnetic force is not uniform in space [33].…”
Section: Concluding Discussionmentioning
confidence: 99%
“…A new cylindrical tundish design that produces a swirling flow in the SEN by using the steel flow potential has been investigated both by water model experiments and numerical simulations [47][48][49]61,67]. This study was the first to try to investigate the influence of such swirling flow tundish design on the steel flow, heat transfer, inclusion motion, and steel/slag interface stability in the mold.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Yang et al found that the swirling flow could force the inclusions to move toward the rotational center and enhance the separation of inclusions from the molten steel to the mold meniscus. Many researchers have been making a lot of efforts to find ways to produce a swirling flow in the SEN . Yokoya et al first proposed the concept of swirling flow in the SEN for steel casting, which could introduce a swirl to the molten steel flowing in the SEN with the swirl blade installed in the SEN.…”
Section: Introductionmentioning
confidence: 99%
“…However, it required to completely redesign the whole tundish system. A device was later designed to be installed in a conventional tundish to produce the swirling flow in the SEN without compromising the structure of the conventional tundish . Nevertheless, the device was too large that was uneconomic.…”
Section: Introductionmentioning
confidence: 99%